The Weimar Republic Sourcebook - Dimendberg, Edward; Jay, Martin; Kaes, Anton (University of California Press, 2020)
Reproduces (translated into English) contemporary documents or writings with an introduction to each section.
Keywords: Germany -- Politics and government -- 1918-1933 -- Sources.; Germany -- Social conditions -- 1918-1933 -- Sources.; Germany -- Social life and customs -- 20th century -- Sources.; National socialism -- Sources.; Government, Resistance to -- Germany -- History -- 20th century -- Sources.; Nazisme -- Sources.; Résistance au gouvernement -- Allemagne -- Histoire -- 20e siècle -- Sources.; Allemagne -- Politique et gouvernement -- 1918-1933 -- Sources.; Allemagne -- Conditions sociales -- 1918-1933 -- Sources.; Allemagne -- Mœurs et coutumes -- 20e siècle -- Sources.; HISTORY / Europe / General.; Social conditions.; Politics and government.; National socialism.; Manners and customs.; Government, Resistance to.; Germany.; Deutschland; Weimar-republiek.; Allemagne -- Vie intellectuelle -- 1918-1945 -- Sources.; Allemagne -- 1918-1933 (République de Weimar) -- Sources.; 1900-1999; History.; Sources.